A conformational study of N-phenyl-1-naphthylamine and 1-anilino-8-naphthalene sulfonate by the empirical method - Kumbar, M.; Maddaiah, V.T. (Biochimica et biophysica acta, 1977)
Conformational analysis of N-phenyl-1-naphthylamine and 1-anilinonaphthalene-8-sulfonate (ANS) was carried out using the empirical method. Properties such as conformational energies and dipole moments were considered. Furthermore, the effect of solvent medium was examined through the effective dielectic constant. The N-phenyl-1-naphthylamine molecule showed two energy minima which were independent of dielectic constant. The ANS molecule also showed two energy minima but the minima changed positions when the dielectic constant increased from 1.0 (vacuum) to 80.0 (highly polar medium). Hydrogen bonding appeared to play an important role in stabilizing these conformations. The minimum energy conformations may have relevance to the binding of ANS to lipid bilayers and bimembranes. The dipole moment, in contrast to the energy minimum, was found to depend on orientation of the sulfonate group rather than of the benzene ring with respect to the naphthalene ring. Thus binding and fluorescence enhancement of ANS may be attributed to the orientation of the sulfonate group, which to a large extent may determine the magnitude of the dipole moment and the degree of electrostatic interactions between the probe and binding domains. Various dimensions like intra-atomic distances, volume and area of the ANS molecule were calculated.